Motivation for Scientific Research of Faculty at the National Defense and Security Training Center belongs to Higger Education Institutions - Quang Duc, Nguyen (VNU Journal of Science: Education Research; Vol 39 No 1SDO - 10.25073/2588-1159/vnuer.4853, 2023)
By reviewing both national and international research on lecturers' scientific research motivation, considering the components of various research models, and incorporating appropriate research results to build a model of factors that affect lecturers' scientific research motivation in a few National Security and Defense facilities based in Ha Noi, this research has investigated these factors based on the data set of 144 responds from various lecturers, in addition to in-depth interviews of 03 lecturers of National Security and Defense Center, Vietnam National University. The analyzed data reveals that suggested elements with varying degrees of influence that contribute to lecturers' scientific motivation are: i) Lecturers' awareness of scientific reasearch; ii) Lecturers' ability to conduct scientific reasearch; iii) Support from Center/Faculty to scientific reasearch; iv) Social issues from the lecturers; and v) Research environment. These factors have mostly contributed to the full explaination of the influence level on lecturers' scientific research motivation.